Testing and Analysis on LTE Base Station Energy Efficiency - Shaoying Li; Zhanhai Zhuang; Weibin Ni (Dianxin kexue)
With the development of LTE network construction, the number of LTE base stations, users and the network traffic are increasing, and energy consumption of network is more prominent, due to the wireless access network energy consumption accounts for over 80% of energy consumption, wherein the base station energy costs accounted for the largest base of operations to become one of the most important expenses for operators. However, there is a lack of effective energy LTE device test methods and test data. To solve this problem, a base model for dynamic load energy consumption was established. According to the energy consumption testing and analysis of LTE base station equipment, control factors that affect the energy efficiency of LTE devices were introduced, different formats and different power station energy efficiency of equipment were compared, and suggestions for planning, procurement, construction, optimization were offered from the energy point of view.